On Optical Solitons of the Fractional (3+1)-Dimensional NLSE With Conformable Derivatives - Korpinar, Zeliha; Tchier, Fairouz; İnç, Mustafa (Frontiers Media Sa, 2020)
In this article, the fractional (3+1)-dimensional nonlinear Shrodinger equation is analyzed with kerr law nonlinearity. The extended direct algebraic method (EDAM) is applied to obtain the optical solitons of this equation with the aid of the conformable derivative. Optical solitons are investigated for this equation with the aid of the EDAM after the nonlinear Shrodinger equation transforms an ordinary differential equation using the wave variables transformation.
Keywords: optical solitons; nonlinear Shrodinger equation; conformable derivative; Kerr law nonlinearity; the extended direct algebraic method